2017
DOI: 10.1080/13825585.2017.1349869
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological tools to predict conversion from amnestic mild cognitive impairment to dementia. The TREDEM Registry

Abstract: Most of the studies about conversion from Mild cognitive impairment (MCI) to dementia have focused on amnestic MCI (aMCI) which is considered a preclinical phase of Alzheimer's disease. The aim of the present study was to identify neuropsychological tools that would best predict conversion from aMCI to dementia. Fifty-five aMCI subjects on the Treviso Dementia Registry were investigated. They underwent a neuropsychological evaluation during their first assessment and again at follow-up. Cox proportional-hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…One possible reason might be that a spatial memory measure was not included in many of previous studies. For example, several recent conversion studies [ 8 , 12 , 13 ] had adopted only verbal memory measures.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason might be that a spatial memory measure was not included in many of previous studies. For example, several recent conversion studies [ 8 , 12 , 13 ] had adopted only verbal memory measures.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, language and semantic memory were assessed using various versions of the Category Fluency test, mainly focusing on the total number of words retrieved. Some studies have reported that individuals who later progressed to dementia generated fewer words than non-converters at baseline evaluation (e.g., [98,99]). In addition, several studies have failed to replicate these findings (e.g., [100,101]).…”
Section: The Prognostic Value Of Measures Of Linguistic-semantic Procmentioning
confidence: 99%
“…Previous studies have reported impaired performance in CFT in Dementia of the Alzheimer's Type (DAT) (Monsch et al, 1992;Henry et al, 2004) and in Mild Cognitive impairment (MCI) (Adlam et al, 2006;Murphy et al, 2006). In this particular population, the impaired performance in CFT has also been reported to be predictive of subsequent progression to dementia (Amieva et al, 2004;Tierney et al, 2005;Hodges et al, 2006;Caroli et al, 2007;Maioli et al, 2007;Aretouli et al, 2011;Hanseeuw and Ivanoiu, 2011;Molinuevo et al, 2011;Blanco Martin et al, 2016;Gallucci et al, 2018), even though some studies have failed to replicate this finding (Alegret et al, 2014;Callahan et al, 2015;Kim et al, 2017;Russo et al, 2017). In more recent years, the performances of individuals with DAT or MCI on CFT have been assessed, taking into account several psycholinguistic variables, modifications in which may reflect a subtle impairment of the lexical-semantic system.…”
Section: Introductionmentioning
confidence: 99%